Comparison of Efficacy of 50% Salicylic Acid Versus Cryotherapy in the Treatment of Plantar Warts - SANDIA BHOJWANI; MUHAMMAD KHURRAM SALAHUDDIN; KANWAL PHULPOTO; SAHAR YAQOOB; SARFRAZ AHMAD; ZILLEHUMA TARIQ (Pakistan Journal of Medical & Health Sciences, 2025)
Aim: To find the comparison of efficacy of 50% salicylic acid versus cryotherapy in the treatment of plantar warts. Methods: Total 85 patients with plantar warts were presented in this study. We divided patients in two groups. 43 patients of group A received 50% salicylic acid and 42 patients received cryotherapy in group B. Outcomes were compared. Results: We found that both treatments were effective in treatment of plantar warts while salicylic acid showed good outcomes as compared to cryotherapy but statistically insignificant. Conclusion: The findings demonstrate that both treatments are similarly effective in achieving wart clearance, with salicylic acid showing a slightly higher, though not statistically significant. Keywords: Plantar warts, salicylic acid, cryotherapy.